PELATIHAN PENDIDIKAN SEKSUAL SEBAGAI UPAYA PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK - Aris Puji Utami; Mariyatul Qiftiyah; Erna Eka Wijayanti (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2019)
Children’s sexual abuse was increasing at Tuban district. Data from the Social Service for Women Empowerment and Child Protection (Dinsos P3A), and NGOs in Tuban District recorded an increase in violence against children, especially victims of sexual abuse from 2013 to 2017, even after Regional Regulation (Perda) Number 13 of 2013 concerning Child Protection was implemented. The impact of cases of sexual violence on children is very severe because it can cause severe trauma, loss of self-confidence, victims will feel hate towards themselves to personality disorders as adults. Methods: One effort that is promoted as an action to prevent incidents of sexual violence against children is an educational workshop sexual abuse in children. The purpose of this community service activity is twofold, namely to increase understanding of sexual education in children and to increase children's awareness of acts of sexual violence, namely to fourth grade students at SDN Gesikharjo Palang Tuban. Result: The workshop was conducted by giving counseling to 86 students grade IV at SDN Gesikharjo Palang Tuban, followed by educational games using giant ladder snake media that have been modified to contain content on sexual education and sexual violence in each box with participants as the pieces to evaluate participants' awareness of sexual violence then closed with a child's self-reflection with a picture of himself to identify the possibility of violence in children. Conclusion: This activity succeeded in increasing the understanding and alertness of grade IV children at SDN Gesikharjo Palang Tuban and finding students who were victims of violence which were then treated by counselors from NGOs caring for children. Suggestions, the government and educational institutions need to launch a sexual education program and increase awareness of sexual violence against minors as an effort to prevent sexual violence against children.